Central neuraxial analgesia for labor: an update of the literature. (September 2017) - Sodha, Serena; Reeve, Alexandra; Fernando, Roshan
Numerous techniques are in use to provide analgesia for labor, of which central neuraxial block is widely considered superior to non-neuraxial options. Central neuraxial techniques have evolved over many years to provide greater efficacy, safety and maternal satisfaction. This narrative review focuses on the literature relating to central neuraxial labor analgesia from the past 5 years, from November 2010 to October 2015. We discuss the evidence related to the various central neuraxial techniques used, the increasingly widespread use of ultrasound guidance and the evidence surrounding other novel methods of central neuraxial block insertion. The timing of institution of central neuraxial analgesia in labor is considered, as are the advances in maintenance regimens for labor analgesia.